Sexual Harassment of College and University Students: A Systematic Review. (October 2021) - Klein, L. B.; Martin, Sandra L.
Increased attention to Title IX and the #MeToo movement has led to more interest in developing strategies to prevent forms of gender-based violence beyond acquaintance rape, including sexual harassment (SH). This study reviewed the extant literature published since 2000 on SH of college/university students ( n = 24) to determine (a) study methods, (b) sample sociodemographic characteristics, (c) prevalence, (d) risk and protective factors, and (e) consequences of campus SH. These studies shared the view that overall SH rates are high, but their findings were difficult to cross-evaluate due to variations in their study designs. Generally, unwanted sexual attention and gender harassment were more commonly experienced in campus SH occurrences than sexual coercion. Findings indicated that being White, a woman, or a sexual minority increased a student's likelihood of experiencing SH while at a college/university. Student SH survivors rarely filed official reports but often faced a variety of mental and physical health consequences. Women of color experienced lower rates of SH but more severe consequences in the aftermath. This review concludes by detailing several implications for future research, as well as possible campus SH prevention, intervention, and policy protocols.